A Novel Blind Channel Estimation Algorithm for a MIMO System - Xia Liu; Bialkowski, M.E.; Shiyang Lu; Hon Tat Hui (VTC Spring 2008 - IEEE Vehicular Technology Conference, 2008)
In this paper, a novel blind channel estimation algorithm for a multiple input multiple output (MIMO) system is described. This algorithm is easier to implement than the previously reported blind estimation algorithms because the channel state information (CSI) is recovered without performing complex mathematical operations such as singular value decomposition (SVD) or eigenvalue decomposition (EVD). The ambiguity associated with the proposed blind estimation is reduced to the phase ambiguity. The proposed channel estimation algorithm is accompanied by new block coding scheme. Using this coding scheme, a block encoder is only required at the transmitter. The proposed scheme is spectral efficient, as it offers the full coding rate when the numbers of transmitting and receiving antennas are equal. The validity of the proposed channel estimation algorithm and coding scheme is verified via computer simulations.